Pricing the cost of an election: the impact of the 2014 elections on stock markets - Carvalho, Augusto de Barros Lisboa de (2016)
What is the effect of elections on real assets? Can we measure the effect on price only observing one outcome? This dissertation attempts to estimate these effects using a methodology based in stock options. The model developed adapts the benchmark Black-Scholes model to incorporate two new parameters: a perfectly anticipated jump in price (∆) and a series of daily probabilities (Θ) reflecting beliefs about outcomes of the election. We apply this method to 2014 Brazilian Presidential Elections and Petrobras - an important oil company in Brazil - using market data from the second election round. The results found show 65-77% difference in company valuation, depending on election outcome. This is equivalent to approximately 2.5% of Brazil’s GDP in 2014.